STUDY OF DIFFERENT BLOOD VESSELS IN THE HEAD AND NECK REGION USING COLOR DOPPLER ULTRASONOGRAPHY AND ITS COMPARISON WITH WESTERN DATA - B. K. BISWAS,; S. PAL,; S. BISWAS,; S. MUKHOPADHYA,; S. NAG, (International Journal of Pharma and Bio Sciences, 2012)
Measurement of blood vessel diameter using Color Doppler Ultrasonography images is a potential methodology in diagnosis, physiological study and is more relevant to the free-vascular tissue transfer surgery. In this study, standard methods of blood vessel diameter of different blood vessels measurement which are relevant to the free tissue reconstructive surgery of face and allied area were adopted. A total of 20 numbers of subjects were selected from the staff members of KPC medical college and Hospital and data of different blood vessels diameter were collected from individual papers published in different journals for comparative study. Finally we develop a chart of mean diameter of different blood vessels, which will be a good reference of the reconstructive surgeon and the industry for the development of microvascular anastomotic devices.